2006
DOI: 10.1080/17461390500440889
|View full text |Cite
|
Sign up to set email alerts
|

Do multidimensional intrinsic and extrinsic motivation profiles discriminate between athlete scholarship status and gender?

Abstract: The purpose of this investigation was to examine whether levels of multidimensional intrinsic, multidimensional extrinsic motivation and amotivation could accurately discriminate scholarship status and gender in United States collegiate athletes. Participants comprised 82 male (M age 0/19.89, SD 0/1.39) and 90 female (M age 0/20.26, SD 0/1.63) collegiate athletes. Each participant completed a demographic questionnaire and the Sports Motivation Scale (Pelletier,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
(129 reference statements)
2
20
1
5
Order By: Relevance
“…1). This result is at odds with previous research in the field of sport motivation of younger athletes [36,37,47]. Compared to co-aged recreational athletes, young athletes involved in competitive sport exhibit lower levels of intrinsic motivation [36].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…1). This result is at odds with previous research in the field of sport motivation of younger athletes [36,37,47]. Compared to co-aged recreational athletes, young athletes involved in competitive sport exhibit lower levels of intrinsic motivation [36].…”
Section: Discussioncontrasting
confidence: 85%
“…Compared to co-aged recreational athletes, young athletes involved in competitive sport exhibit lower levels of intrinsic motivation [36]. Similarly, among young competitive athletes, higher performers exhibit higher levels of extrinsic motivation and amotivation than lower performers [37], and scholarship athletes exhibit less self-determined forms of motivation than non-scholarship athletes [47]. The cited authors suggested that high competitive pressure and rewards in sport may cause a shift toward a perceived external locus of causality in the athlete, which leads to a decrease in intrinsic motivation and an increase in extrinsic motivation and amotivation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, though mixed findings have been reported regarding sex-related differences (Amorose & Horn, 2000), women tend to report more intrinsic motivation than men (Chantal, Guay, Dobreva-Martinova, & Vallerand, 1996;Fortier et al, 1995;Kingston, Horrocks, & Hanton, 2006). Sport type is also an important consideration.…”
Section: Motivationmentioning
confidence: 94%
“…Scholarship status was a discriminating factor in studies that considered the motivation of intercollegiate athletes in the United States. Again, however, the findings were mixed: some have reported that scholarship athletes have less self-determined motivational profiles than non-scholarship athletes (Kingston et al, 2006), others have claimed the opposite (Amorose & Horn, 2000), and a third group has reported no difference (Amorose & Horn, 2001).…”
Section: Motivationmentioning
confidence: 94%
“…Os mesmos autores ainda revelam que as três necessidades intrínsecas apresentam "equifinalidade", ou seja, elas são interdependentes e o desenvolvimento de uma gera o desenvolvimento das outras. É de salientar que outros estudos que relacionam o género com a motivação foram desenvolvidos em culturas diferentes, tendo demonstrado que não existe um consenso acerca dessa relação, isto é, não existe uma relação direta entre a variável género e as dimensões propostas pela autodeterminação (Fortier, Vallerand, Brière & Provencher, 1995;Halbrook, Blom, Hurley, Bell & Holden, 2012;Kingston, Horrocks & Hanton, 2006;Krinanthi, Konstantinos & Andreas, 2010;Pero et al, 2009).…”
Section: Introduçaounclassified